A national survey integrating clinical, laboratory, and WASH data to determine the typology of trachoma in Nauru. - Kathleen D Lynch; Sue Chen Apadinuwe; Stephen B Lambert; Tessa Hillgrove; Mitchell Starr; Beth Catlett; Robert S Ware; Anasaini Cama; Sara Webster; Emma M Harding-Esch; Ana Bakhtiari; Robert Butcher; et al. (PLoS Neglected Tropical Diseases, 2022)
Background The epidemiology of trachoma in several Pacific Islands differs from other endemic settings, in that there is a high prevalence of clinical signs of trachoma, particularly trachomatous inflammation-follicular (TF), but few cases of trichiasis and limited evidence of ocular chlamydial infection. This so-called "Pacific enigma" has led to uncertainty regarding the appropriate public health response. In 2019 alongside Nauru's national trachoma population survey, we performed bacteriological and serological assessments of children to better understand the typology of trachoma and to determine whether there is a need for trachoma interventions. Methods We used two-stage cluster sampling, examining residents aged ≥1 year and collecting household-level water, sanitation, and hygiene (WASH) variables. Children aged 1-9 years provided conjunctival swabs and finger-prick dried blood spots to investigate the presence of Chlamydia trachomatis nucleic acid and anti-Pgp3 antibodies, respectively. Principal findings In 818 participants aged 1-9 years, the age-adjusted TF prevalence was 21.8% (95% CI 15.2-26.2%); ocular C. trachomatis prevalence was 34.5% (95% CI 30.6-38.9), and anti-Pgp3 antibody prevalence was 32.1% (95% CI 28.4%-36.3%). The age- and gender-adjusted prevalence of trichiasis in ≥15-year-olds was 0.3% (95% CI 0.00-0.85), but no individual with trichiasis had trachomatous scarring (TS). Multivariable analysis showed an association between age and both TF (OR per year of age 1.3 [95% CI 1.2-1.4]) and anti-Pgp3 positivity (OR 1.2 [95% CI 1.2-1.3]). There were high rates of access to water and sanitation and no WASH variable was associated with the presence of TF. Conclusions TF, nucleic acid, and age-specific antibody prevalence collectively indicate that high levels of C. trachomatis transmission among children present a high risk of ocular damage due to trachoma. The absence of trichiasis with trachomatous scarring suggest a relatively recent increase in transmission intensity.